Кримськотатарський національний рух: історична ретроспектива XX–XXI ст. - Афанасьєва, Мар’яна Володимирівна; Афанасьєва, М. В.; Афанасьева, Марьяна Владимировна; Afanasieva, Mariana V.; Кормич, Людмила Іванівна; Кормич, Л. І.; Кормич, Людмила Ивановна; Kormych, Liudmyla I.; Кулі-Іванченко, Ксенія Костянтинівна; Кулі-Іванченко, К. К.; Кули-Иванченко, Ксения Константиновна; Kuli-Ivanchenko, Kseniia K. (Київський політехнічний інститут ім. Ігоря Сікорського, 2019)
У статті проаналізовано розвиток кримськотатарського національного руху в історичній ретроспективі. На підставі історичних подій та документів XX–XXI ст. встановлено, що активізація діяльності національного руху збігалася з революційними настроями народів Російської імперії (1917), Радянського Союзу (1990) та України (2014). Обґрунтовується висновок, що історія національного руху корінного народу Криму постійно супроводжувалася боротьбою за право створювати свої національні органи самоврядування.

According to the UN, there are approximately 300–500 million indigenous peoples in the world, occupying 20% of the globe. Despite the breadth of differences between indigenous peoples around the world, they have one thing in common – they share past injustices against them. The Crimean Tatars, the indigenous people of Ukraine, have not missed this fate. The purpose of the article is to reveal the main historical stages of the development of the Crimean Tatar national movement during the 20th — 21st cent. The research methodology is based on the principles of historicism, systemicity, scientific objectivity, as well as the application of general scientific (analysis, synthesis, deduction, induction, generalization), as well as special historical (problem historical, historical systemic, problem chronological, historical and typological) methods. The scientific novelty of the article is that for the first time, on the basis of analysis of historical events and documents for the period of the 20th — 21st cent., it has been established that the activation of the activities of the national representative bodies of the Crimean Tatar people – the Kurultay and Mejlis – is historically connected with the revolutionary sentiments among the peoples of the Russian Empire (1917), the Soviet Union (1990) and Ukraine (2014), aimed at preserving national identity and the practical realization by Crimean Tatars of their fundamental right to self-determination. Summing up, the analysis shows that the centennial history of the national movement of the Crimean Tatars was constantly accompanied by the struggle for the right to preserve and strengthen their political and legal national institutions.
The Crimean Tatar National Movement: a Historical Retrospective (20th — 21st Cent.)
Афанасьєва М. В. Кримськотатарський національний рух: історична ретроспектива XX–XXI ст. / М. В. Афанасьєва , Л. І. Кормич, К. К. Кулі-Іванченко // Сторінки історії: збірник наукових праць. – Вип. 48. - Київський політехнічний інститут імені Ігоря Сікорського, 2019. – С. 252-263. (Afanasieva M. V. The Crimean Tatar National Movement: a Historical Retrospective (20th — 21st Cent.) / М. V. Afanasieva, L. I. Kormych, K. K. Kuli-Ivanchenko // History Pages. - Vol. 48. - Igor Sikorsky Kyiv Polytechnic Institute, 2019. – P. 252-263.)
Keywords: корінний народ; Крим; кримськотатарський народ; Курултай; Меджліс; національний рух; окупація; indigenous people; Crimea; Crimean Tatar people; Kurultai; Mejlis; national movement; occupation; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects